A natureza humana e a liberdade na formação do homem de Jean-Jacques Rousseau - Lima, Nahyane Nogueira de (2018)
The present work concerns about the notion of human nature and liberty in order to reflect how these properties influence the formation of the man. Considering that the subjects developed are part of a greater whole, we thought it would be important to analyze the conjuncture that lead Rousseau to develop the philosophy that made him to become one of the greatest names of the eighteenth century. For this reason, our research initially intend to understand the targets of the harsh criticisms made by the philosopher in his writings –which includes the social and political environment and the notions of men he rejects. Afterward the criticism, we present the notion of man provided by the genevan, a man who does have innate characteristics, but this does not made him a determinate being because he also brings with him the possibility of becoming another or improve himself, which moves us to close the research. Associated to his undeniable pessimism, Rousseau was also a nonconformist about society and the notions of a man proclaimed at that time, however while his pessimism led him to deny that society, his disagreement provoked him to present a possibility of man impelling him also to propose a restructuring that goes from morality to politics, taking nature as a guide and freedom as a path whereby and for which the man must be directed